Efeito da fotobiomodulação e corticoide sobre a inflamação crônica pulmonar em modelo experimental de asma - Nascimento, Cristiano Rodrigo de Alvarenga (2020)
Asthma affects a significant portion of the population, resulting in a socio- economic problem. Studies on treatment with corticosteroids have contributed at different levels to the treatment of asthma, as well as its deleterious effects. Photobiomodulation (FBM) is a therapy that demonstrates effectiveness in lung diseases by reducing inflammatory parameters, with low cost and without side effects. Thus, the present study aimed to evaluate the effects of FBM and its combination with nasal corticosteroids (CORT) in an experimental model of chronic pulmonary allergic inflammation induced by ovalbumin (OVA). Balb/C mice were divided into 7 groups: Basal, CORT, FBM, OVA, OVA + CORT, OVA + FBM, OVA + CORT + FBM. Chronic allergic pulmonary inflammation was induced by subcutaneous (SC) immunization of ovalbumin (OVA), mixed with alum (days 0 and 14), and orotracheal challenge with OVA (three days / week for five weeks). The OVA + FBM Group was irradiated (diode laser, 660nm, 30mW and 3J), OVA + CORT was treated with fluticasone furoate (0.0275mg / dose) intranasally and the OVA + CORT + FBM group was treated with CORT and FBM (one hour before the OVA orotracheal challenge we treated with CORT and one hour later with FBM). Twenty-four hours after the last treatment, the animals were anesthetized, tracheotomized, cannulated and the bronchoalveolar lavage collected and analyzed (total and differential cell count, as well as cytokine levels using the ELISA technique). Both treatments reduced the total number of cells, macrophages, neutrophil lymphocytes and eosinophils in bronchoalveolar lavage (BAL), except for macrophages in the OVA+FBM group, were the treatment with CORT do not decrease the number of these cells. With the use of FBM there was a reduction in the production of IL-4, IL-5, IL-1, TNF- and IL-13 and an increase in IL-10 in BAL also in all treated groups. We also observed that in the OVA+CORT, OVA+FBM and OVA+CORT+FBM groups, there was no increase in collagen deposition, mucus production and tracheal hyperreactivity that was observed in the OVA group. In this way, we demonstrate that both therapies are efficient, yet photobiomodulation alone or associated with conventional treatment seems to have a promising role for the treatment of asthma.